The asset administration shell as enabler for predictive maintenance: a review - Jhonny Rodriguez Rahal; Alexander Schwarz; Benjamín Sahelices; Ronny Weis; Simon Duque Antón (Journal of Intelligent Manufacturing, 2023)
Abstract The emergence of the Internet of Things and the interconnection of systems and machines enables the idea of Industry 4.0, a new industrial paradigm with a strong focus on interaction and communication between physical and digital entities, leading to the creation of cyber-physical systems. The digital twin and the standard for the Asset Administration Shell are concepts derived from Industry 4.0 that exploit the advantages of connecting the physical and virtual domains, improving the management and display of the collected data. Furthermore, the increasing availability of data has enabled the implementation of data-driven approaches, such as machine and deep learning models, for predictive maintenance in industrial and automotive applications. This paper provides a two-dimensional review of the Asset Administration Shell and data-driven methods for predictive maintenance, including fault diagnosis and prognostics. Additionally, a digital twin architecture combining the Asset Administration Shell, predictive maintenance and data-driven methods is proposed within the context of the WaVe project.
Keywords: 330; Asset administration shell; Predictive maintenance; Digital twin; Machine learning; Industry 4.0; WaVe